Amoral Gower : language, sex, and politics - Watt, Diane, 1965- (Medieval cultures ;, 2003)
Drawing on a combination of queer and feminist theory, ethical criticism, and psychoanalytic, historicist, and textual criticism, Diane Watt focuses on the language, sex, and politics in Gowers writing. She demonstrates that Gower engaged in the sort of critical thinking more commonly associated with Chaucer and William Langland and contributes to modern debates about the ethics of criticism.